1989
DOI: 10.1523/jneurosci.09-10-03410.1989
|View full text |Cite
|
Sign up to set email alerts
|

GABAergic neurons in the rat hippocampal formation: ultrastructure and synaptic relationships with catecholaminergic terminals

Abstract: Numerous studies indicate that gamma-aminobutyric acid (GABA) can either hyperpolarize or depolarize hippocampal pyramidal and granule cells. While the inhibitory action of GABA may occur directly on these cells, the excitatory action may be mediated by interactions of GABAergic neurons with each other or with catecholaminergic afferents. We sought to examine the cellular basis for these interactions and their relative frequency. Thus, the ultrastructural morphology of GABAergic neurons and their relation to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

1991
1991
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(42 citation statements)
references
References 58 publications
1
41
0
Order By: Relevance
“…Anatomical data support models I and II, in that a significant portion of GABAergic terminals in the hippocampus form synapses on the same perikarya or dendrites as the noradrenergic terminals (model I), and that there is a close apposition between GABAergic and noradrenergic terminals (model II) (Milner & Bacon, 1989). Electrophysiological data have shown that there is precedence for noradrenaline modulation of both excitatory and inhibitory synaptic transmission.…”
Section: Adrenergic Receptorsmentioning
confidence: 61%
“…Anatomical data support models I and II, in that a significant portion of GABAergic terminals in the hippocampus form synapses on the same perikarya or dendrites as the noradrenergic terminals (model I), and that there is a close apposition between GABAergic and noradrenergic terminals (model II) (Milner & Bacon, 1989). Electrophysiological data have shown that there is precedence for noradrenaline modulation of both excitatory and inhibitory synaptic transmission.…”
Section: Adrenergic Receptorsmentioning
confidence: 61%
“…The effect of picrotoxin is not seen when the p adrenoceptor antagonist, timolol, is co-administered, which suggests that GABAergic synapses in amygdala, septum, and hippocampus are modulated by P-adrenoceptor synapses [Izquierdo et al, 19921, a possibility that is sustained by neuroanatomical findings [Leranth and Frotscher, 1989;Milner and Bacon, 1989;Nieuwenhuys, 19851. Muscimol [Castellano and McGaugh, 19901, bicuculline [Brioni and McGaugh, 19881, and picrotoxin [ McGaugh et al, 19901 are also effective when given systemically. So are most of the benzodiazepines (BZs) (diazepam, chlordiazepoxide, clonazepam), which bind to a specific site of the GABA, receptor arid allosterically enhance the action of GABA or muscimol.…”
Section: Recent Pharmacological Findings Linking Ltp and Memory Storagementioning
confidence: 99%
“…As commented above, evidence suggests that P-adrenoceptor [ Hopkins and Johnston, 19881 and muscarinic cholinergic receptor [Lin and Phillis, 1991;Markram and Segal, 19921 are involved in the induction of LTP. Abundant neuroanatomical evidence suggests convergence of glutamatergic, GABAergic, cholinergic, and noradrenergic fibers onto hippocampal, amygdala, or septa1 neurons [Leranth and Frotscher, 1989;Milner and Bacon, 1989;Nieuwenhuys, 19851.…”
Section: Recent Pharmacological Findings Linking Ltp and Memory Storagementioning
confidence: 99%
“…Most commonly, varicosities lack postsynaptic specializations and are thought to act functionally by volume transmission (Agnati et al, 1995). However, when synapses are established, GABAergic interneurons are often the preferential postsynaptic targets (Milner and Bacon, 1989). Although both ␣1 noradrenergic receptormediated suppression of a potassium conductance (Bergles et al, 1996) and ␤ noradrenergic receptor-dependent increase of the hyperpolarization-activated current (Maccaferri and McBain, 1996) have been observed in a variety of interneurons, the complete actions of noradrenaline on hippocampal GABAergic networks are not fully understood.…”
Section: Introductionmentioning
confidence: 99%